ANALISA PEMBENTUKAN ALIGNMENT LENGKUNG DOWN TRACK KM 9+252,621 – 9+820 ANTARA STASIUN ASEAN-SENAYAN MRT JAKARTA DENGAN METODE TIGA TITIK (STRING) - Sudarwati; Dwi Nurdianto (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2020)
On the track curve, you must always pay attention to the alignment of the rail so that the track when being traversed by the train becomes comfortable and of course safe for train travel. The wear on the rails must occur on the rails, especially on the arch, so it is necessary to periodically replace the rails according to the radius and also the bending life.The process of collecting data can be divided into two, namely primary data and secondary data. Primary data is obtained by direct observation in the field (observation), and by interviewing the related parties who carry out the construction of the railroad arch. Meanwhile, secondary data is supporting data in this study. Secondary data were obtained from literature books, documentation, libraries, or as a buid drawing of the arch. Based on the data obtained from the field data and as build drawing then it is applied to the arrow formula and the height to obtain the appropriate alignment and height in the curve.The results of this study obtained a calculation of horizontal alignment and a height of 2.5 m to form an alignment of an arc that is suitable, safe, and comfortable for trains to pass.